Implementation of blended learning model in mathematics subject - Azimmah, Aulia Nurul; Murtiyasa, Budi (Universitas Islam Raden Intan Lampung, INDONESIA, 2022)
Technology helps optimize the learning process. PMRI-based e-modules can help students in the online learning process. This study aimed to produce e-module teaching materials based on Indonesian realistic mathematics education for class VII social arithmetic that are valid, practical, and effective. The application used is Flip PDF Professional, which involves 63 research subjects at one of the state middle schools in the Banyuasin district. The instruments used were validation sheets, student response questionnaires, and student tests. This research uses the type of development research model called the ADDIE model, which has five stages: namely analysis, design, development, implementation, and evaluation. Based on the validation results by three validators, the development of PMRI-based e-module teaching materials is included in the valid criteria with an average value of 84.36%. According to the results of the practicality questionnaire, the average value is 80.39%. Students achieve an average score of 85% on the effectiveness criteria in the final test, indicating that the development results are suitable for use in the learning process. The e-module teaching materials that have been developed will provide convenience in the learning process both offline and online, which will have an impact on increasing student learning outcomes and can be used as a consideration for teachers in delivering material, especially social arithmetic class VII.